Pengaruh Karakteristik Perusahaan Terhadap Nilai Perusahaan Dan Pengungkapan Informasi Sosial Sebagai Variabel Intervening - Farida Ikhwandarti; Suryo Pratolo; Rudy Suryanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
The research was conducted to identify the social information disclosure on the companies listed in the Indonesian Stock Exchange at 2003-2007 and to analyze the effect of the companies characteristics toward firm value and the social information disclosure as the intervening variable. The companies characteristics consisting of the percentage of management ownership, leverage, company size, industry type and profitability were used as exogenuous variable and the social information disclosure all at once used as intervening variable. The endogenuous variable in this research were the firm value. The social information disclosure has focused on the voluntary disclosure. The voluntary disclosure on this research applied the annual reports which were measured by 32 items, while the procedures used were adopted from Glouter in Utomo (2000) and Rika and Islahuddin (2008). The statistical method used in this research was path analysis. This research used 267 sample companies non-financial sector listed and registered in the Indonesian Stock Exchange in 2003-2007. The result of this research showed that the industry types have significant effect toward the social information disclosure, the percentage of management ownership have significant effect toward the firm value and the industry types have significant effects toward the firm value.